2009
DOI: 10.3174/ajnr.a1607
|View full text |Cite
|
Sign up to set email alerts
|

Endovascular Treatment of Epistaxis

Abstract: SUMMARY:Epistaxis is a common condition that can be managed conservatively in most cases. When these measures, including anterior and posterior packing of the nasal cavity, are unsuccessful at controlling the bleeding, interruption of the blood supply to the sinonasal area can be performed, either by surgical ligation or by transarterial embolization. Embolization should be preceded by thorough diagnostic angiography. Aside from aiding with subsequent selective catheterization and embolization, such angiograph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
110
1
4

Year Published

2010
2010
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(115 citation statements)
references
References 66 publications
0
110
1
4
Order By: Relevance
“…The traditional treatment strategy of posterior nasal packing has been largely replaced by the more effective and less morbid techniques of transnasal endoscopic sphenopalatine artery ligation (TESPAL) [1][2][3] and endovascular arterial embolization. [4][5][6] Furthermore, a recent study by Dedhia et al 7 suggested that TESPAL is the most cost-effective strategy compared with posterior nasal packing. The success rates for both TESPAL and embolization is estimated to be greater than 90%, and therefore the decision to choose one modality over another can be challenging.…”
mentioning
confidence: 99%
“…The traditional treatment strategy of posterior nasal packing has been largely replaced by the more effective and less morbid techniques of transnasal endoscopic sphenopalatine artery ligation (TESPAL) [1][2][3] and endovascular arterial embolization. [4][5][6] Furthermore, a recent study by Dedhia et al 7 suggested that TESPAL is the most cost-effective strategy compared with posterior nasal packing. The success rates for both TESPAL and embolization is estimated to be greater than 90%, and therefore the decision to choose one modality over another can be challenging.…”
mentioning
confidence: 99%
“…Angioembolisation has been an accepted technique in the management of refractory epistaxis [3,4]. It is especially sought in cases of posterior epistaxis, which fails to respond to nasal packing and medical measures.…”
Section: Discussionmentioning
confidence: 99%
“…Embolising agents used to treat traumatic oro-nasal bleeding includes pledgets of gelatin sponge and stainless steel or platinum coils [3,12]. Gel foam particles are the most commonly used embolising agents.…”
Section: Discussionmentioning
confidence: 99%
“…110, 111 The complication rates and success of embolization or surgical ligation are similar, though embolization is associated with more major complications when embolic agents inadvertently enter the internal carotid or ophthalmic artery.…”
Section: Intravascular Sonographymentioning
confidence: 99%